Subdural drainage techniques for single burr-hole evacuation of chronic subdural hematoma: two drains frontal-occipital position versus one drain frontal position. (4th May 2021) - Wu, Qiangjun; Liu, Qin; Chen, Duoning; Chen, Zhufeng; Huang, Xuecai; Luo, Ming; He, Shike
Abstract: Objective: Burr-hole craniostomy with a closed drainage system is the most commonly used technique for chronic subdural hematoma(CSDH), but the reoperation rate for hematoma recurrence is still high. This retrospective study aimed to compare the complications and recurrence of two subdural drains placement with tips frontal-occipital position (TFOP) versus one subdural drain placement with tip frontal position(OFP) following single burr-hole evacuation for the treatment of chronic subdural hematoma(CSDH). Methods: The authors analyzed data of all CSDH patients who underwent single burr-hole surgery with placement of subdural closed-drainage system(TFOP or OFP techniques) between January 2013 and December 2017. Data analysis included general patient data, complications, recurrence and clinical outcome. Results: A total of 331 patients were included(85 TFOP and 246 OFP). The TFOP group and OFP group were statistically comparable with respect to baseline characteristics except for preoperative Markwalder score ( p  = 0.019). Midline shift and subdural fluid thickness on first postoperative day were greater in OFP group than the TFOP group ( p  = 0.028; and p  = 0.007, respectively). In addition, patients with OFP had a lower percent of hematoma change after surgery and much more residual subdural air than those with TFOP ( p  = 0.001; and p  < 0.001, respectively). Postoperative complications and clinical outcome between the two groups showed no significant differences. During the 3-month follow-up, the rate of hematoma recurrence was significantly lower among patients treated with TFOP than those treated with OFP ( p  = 0.039). Conclusions: The postoperative complications rate did not differ between TFOP group and OFP group for patients with CSDH. Considering the lower rate of recurrence, TFOP following single burr-hole evacuation might be a safe and promising option for CSDH treatment.